Molecular Research in Human Microbiome - Mascellino, Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint turns out to be very important for the pathologies deriving from the gut microbiome and its disorders. Human health seems to be correlated with the status of our microbiome, which plays a vital role in our health. The human microbiome is associated with a wide range of diseases, from non-neoplastic to tumorigenesis, including cancer, inflammation, intestinal damage, etc. Following these statements, it is possible to deduce the paramount importance of the role of the gut microbiome and the relative consequences for human well-being.